PENGARUH ELECTRONIC WORD OF MOUTH ( E-WOM )TERHADAP MINAT BELI SABUN SEOM GUM - Ndraha, Arlisman (Universitas Nias Raya, 2024)
The purpose of this study was to determine the effect of motivation on the effectiveness of employee work at the Hilimegai Sub-district Office, South Nias Regency. The type of research used is the quantitative type. The source of data is from employees by using questionnaires. Data collection techniques are questionnaire techniques, documents such as books, journals and photos. The population and sample of this study were as many as 30 respondents. Simple regression analysis with values was used to analyze the data of Y = 12.981 + 0.531X. Based on the results of the t test in this study that the calculated value was 8,457>ttable 1,702, so that researchers can conclude that there is an influence of work motivation on the effectiveness of employee work at the Hilimegai Sub-district Office, South Nias Regency. The suggestions of this study are (1) To increase employee motivation, it is necessary for organizations to create a conducive environment so that it makes them comfortable to do work. (2) The working atmosphere needs to be improved in accordance with the wishes of employees in order to increase employee work motivation.